A video parent-training program for families of children with autism spectrum disorder in Albania. (December 2018) - Dai, Yael G.; Brennan, Lynn; Como, Ariel; Hughes-Lika, Jamie; Dumont-Mathieu, Thyde; Carcani-Rathwell, Iris; Minxhozi, Ola; Aliaj, Blerina; Fein, Deborah A.
Highlights: A novel, video-based parent-training program was developed in Albanian for parents of young children with ASD. Parents of children with ASD in Albania rated this training program as enjoyable and valuable. The program modestly increased an aspect of self-efficacy as well as parents' knowledge of effective teaching strategies. Abstract: Background: Behavioral intervention with parent participation is effective in reducing symptoms of Autism Spectrum Disorder (ASD), but access to intervention is limited. The current study explored whether a video-enriched parent-training program would (a) be comprehensible and acceptable to parents in the Republic of Albania, (b) increase parental knowledge of behavioral strategies, and (c) increase parental self-efficacy. Methods: Twenty-nine parents of children with ASD aged 18–70 months completed the Early Intervention Parenting Self-Efficacy Scale (EIPSES, Guimond et al., 2008) and a quiz to assess their knowledge of behavioral strategies. Parents in the Treatment Group then received access to a parent-training (PT) program on evidence-based teaching and behavior management techniques. The program was based on empirical research, but considered Albanian cultural norms and included topics Albanian parents requested. Parents in the Treatment Group rated the program using the Treatment Evaluation Inventory Short Form (TEI-SF; Kelley et al., 1989). Change in parents' quiz scores and EIPSES ratings from baseline to post-treatment were compared by group. Results: Parents rated this video training program as comprehensible and valuable. The program modestly increased aspects of self-efficacy as well as parents' knowledge of effective teaching strategies. Conclusion: Remote PT may be useful in low-resource settings to help parents develop techniques for teaching skills and forestalling problem behavior in children with ASD. Additional research, with a larger sample size, that observes the effect of the program on child behavior is warranted.